Photon parameters for gamma-rays sensing properties of some oxide of lanthanides - Issa, Shams A. M.; Sayyed, M. I.; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin (Elsevier, 2018)
In the present research work, the mass attenuation coefficients (μm) representing the interaction of gamma photons with some oxide of lanthanides (Lu2O3Yb2O3, Er2O3, Sm2O3, Dy2O3, Eu2O3, Nd2O3, Pr6O11, La2O3 and Ce2O3) were investigated using WinXCom software in the wide energy range of 1 keV–100 GeV. The calculated values of μm afterwards were used to evaluate some gamma rays sensing properties as effective atomic effective atomic numbers (Zeff), effective electron densities (Nel), half value layer (HVL) and mean free path (MFP). The computed data observes that, the Lu2O3 shown excellent γ-rays sensing response in the broad energy range. At the absorption edges of the high elements present in the lanthanide compounds, more than a single value of Zeff were found due to the non-uniform variation of µm. Comparisons with experiments wherever possible have been achieved for the calculated µm and Zeff values. The calculated properties are beneficial expanded use of designing in radiation shielding, gas sensors, glass coloring agent and in electronic sensing devices.